Grassland allergenicity increases with urbanisation and plant invasions - Maud Bernard-Verdier; Birgit Seitz; Sascha Buchholz; Ingo Kowarik; Sara Lasunción Mejía; Jonathan M. Jeschke (Ambio, 2022)
Pollen allergies have been on the rise in cities, where anthropogenic disturbances, warmer climate and introduced species are shaping novel urban ecosystems. Yet, the allergenic potential of these urban ecosystems, in particular spontaneous vegetation outside parks and gardens, remains poorly known. We quantified the allergenic properties of 56 dry grasslands along a double gradient of urbanisation and plant invasion in Berlin (Germany). 30% of grassland species were classified as allergenic, most of them being natives. Urbanisation was associated with an increase in abundance and diversity of pollen allergens, mainly driven by an increase in allergenic non-native plants. While not inherently more allergenic than native plants, the pool of non-natives contributed a larger biochemical diversity of allergens and flowered later than natives, creating a broader potential spectrum of allergy. Managing novel risks to urban public health will involve not only targeted action on allergenic non-natives, but also policies at the habitat scale favouring plant community assembly of a diverse, low-allergenicity vegetation. Similar approaches could be easily replicated in other cities to provide a broad quantification and mapping of urban allergy risks and drivers.